DARK WEB − AS CHALLENGE OF THE CONTEMPORARY INFORMATION AGE. - Denic, Nenad V.; Devetak, Sasa (TRAMES: A Journal of the Humanities & Social Sciences, 2023)
Reconnaissance and monitoring activities of actors on the Internet are becoming indispensable security tools for governments around the world. The Deep Web as part of the Internet protects actors. However, cheap and reliable encryption and online identity protection have become attractive to state and non-state actors in the cyber domain. Unfortunately, part of the Deep Web, the Dark Web is now offering to training terrorists, and trading arms and illicit substances. The Dark Web represents a communication and information systems infrastructure where actors are anonymous and the services are adaptable to the demands of geopolitical circumstances. This paper analyzes the ways of using the Dark Web and its impact on the information environment since the global war on terrorism began, through a period when humanity struggled with Covid-19 pandemic to the war in Ukraine.